Motivations Influencing the Intention to Take Examination for Governmental Personnel of Gen Z in the Northeast Region by Thai University Students - Chantaplaboon, Natthayanee; Pothiboonrueng, Chantira (Trends of Humanities and Social Sciences Research, 2023)
The research aimed to study the motivations influencing the intention to take the examination to be governmental personnel of Generation Z in the Northeast Region of Thailand. The research was done quantitatively. The sample was Generation Z in the Northeast Region who intended to take the examination by applying the quota sampling method of 500 samples from education institutions in the 20 Northeastern provinces. The research instrument was a questionnaire, divided into 3 parts: the general information applied checklist method; the motivations and intention to take examination applied 5-scale of Likert scale. The questionnaire has a reliability value of 0.89. The data analysis was done using frequency, percentage, mean, and standard deviation for general information and the level of motivations and intention, and multiple regression analysis was applied to analyze the relationship between the motivations and intention to take the examination. There were 401 completed questionnaires that were taken for further analysis. The findings presented that Generation Z had the overall motivation to take the examination at the low level ( = 2.51, S.D. = 1.21), and had the intention to take the examination at the medium level ( = 2.71, S.D. = 1.10). The motivations influencing the intention to take the examination to be governmental personnel of Generation Z in the Northeast Region of Thailand were cultural motivation (Beta = 0.26), personal motivation (Beta = 0.25), psychological motivation (Beta = 0.24), and societal motivation (Beta = 0.16). The suggestion was that the family played a very important role in Gen Z’s decision and they should foster their children to serve in the public sector in order to make a change in the society and the country.